2017
DOI: 10.1021/acs.macromol.7b01290
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Preference in Multilayer Block Copolymer Nanomeshes with Respect to Layer-to-Layer Commensurability

Abstract: We present a combination of self-consistent field theory simulations and experimental results to explore the mechanism behind the orientational preference of second-layer cylinders in nanomeshes formed by two consecutive steps of the self-assembly of block copolymers (BCPs). Incommensurability of the top-layer cylinder spacing with that of the bottom-layer features is found to dictate orientation preference, and this mismatch can be controlled by either the film height or the nanomesh spacing ratio via the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In general, supramolecular columns favor homeotropic orientations on the solid-to-solid interface, , and this orientation behavior has been observed in other topographic confinement applications, such as in rectangular microchannels and sandwich systems. ,,, Thus, it is expected that the triangular grooves should serve as a topographical confinement feature to trigger the orthogonal alignment of supramolecular columns relative to the facet surface. In addition, the triangular grooves impose severe packing constraints on the columns near the boundary of the facets. In particular, the high stress on the columns oriented parallel to the ridge direction incurs energetic penalties due to the mismatch in the hexagonal column packing. Therefore, the orientation behavior occurs to alleviate the packing frustration, and thus, the supramolecular columns become aligned in the ridge direction.…”
Section: Resultsmentioning
confidence: 99%
“…In general, supramolecular columns favor homeotropic orientations on the solid-to-solid interface, , and this orientation behavior has been observed in other topographic confinement applications, such as in rectangular microchannels and sandwich systems. ,,, Thus, it is expected that the triangular grooves should serve as a topographical confinement feature to trigger the orthogonal alignment of supramolecular columns relative to the facet surface. In addition, the triangular grooves impose severe packing constraints on the columns near the boundary of the facets. In particular, the high stress on the columns oriented parallel to the ridge direction incurs energetic penalties due to the mismatch in the hexagonal column packing. Therefore, the orientation behavior occurs to alleviate the packing frustration, and thus, the supramolecular columns become aligned in the ridge direction.…”
Section: Resultsmentioning
confidence: 99%
“…(Rahman et al, 2016) Spontaneous orthogonal alignment of BCP thin films can be attributed to the polymer chain stretching or compression causing entropic energy penalty when lamellar BCP domains align in parallel with the underlying corrugation. (Carpenter et al, 2017); (Han et al, 2010) Metal oxide thin-film nanoarchitectures can also be realized by combining VPI with spontaneous orthogonal self-alignment of successively stacked lamellar BCP patterns. The spontaneous orthogonal alignment process can be easily applied to a large area by using simple starting templates that do not require specially engineered substrates or complicated pre-processing.…”
Section: Vapor-phase Infiltration Of Functional Materialsmentioning
confidence: 99%
“…(Al Hossain et al, 2020) AlO x nanodots created by infiltration synthesis in self-assembled PS-b-PMMA could be also integrated into polymer solar cells for improving device power conversion efficiency by increasing the light absorption by optical scattering and charge collection by creating a protruded electrode structure. (Carpenter et al, 2017) CONCLUSION Self-assembled BCP thin films have emerged as a nontraditional material patterning platform, when combined with strategies to convert these nanomorphologies into more useful functional inorganic nanostructures for applications in nanodevices. Various post-self-assembly modification processes, including thin-film deposition and lift-off, VPI and LPI hybridization, and plasmaetching-based pattern transfer, have enabled the generation of various nanostructured semiconductors, metals and conductive polymer nanostructures for various device applications such as in opto-chemical sensors, solar cells.…”
Section: Infiltration-modified Block Copolymer Films For Lithographic Pattern Transfer Into Functional Substratesmentioning
confidence: 99%
“…Man et al 29,30 systematically studied the self-assembly of lamellar forming BCP thin film on a sinusoidal substrate, and showed an enhanced synergy between substrate topography combined with a weak surface preference to obtain defect-free perpendicular lamellar BCP thin films. Recently, Carpenter et al 31 presented a study combining SCFT calculations with experimental results, and found that the orientation of cylinders with respect to the trench depends on the commensurability of the BCP hexagonal packing with the substrate characteristic length and film thickness.…”
Section: Introductionmentioning
confidence: 99%